Providing effective innovative strategies in the development of cosmetics industry with emphasis on international entrepreneurship - Ali Khabaz; Jamshid Edalatian shahryari; Heydar Amiran (ارزش آفرینی در مدیریت کسب و کار)
AbstractThe aim of the present research is to present effective innovative strategies in the development of cosmetics industry with an emphasis on international entrepreneurship. The research method is applicable in terms of its purpose, and qualitative in terms of its implementation. The statistical population of the research includes 7 managers and officials of Sehat Industrial and Trading Company and 3 academic experts. The data collection tool is interview. To analyze the research data, theme analysis; which is a method to determine, analyze, and express of the patterns (themes) in the data, as well as MAXQDA software was used. According to the obtained results, the innovation strategies are: aggressive innovative strategies, innovative technology absorption strategies, pioneering innovative strategies, risky innovative strategies, among which the innovative technology absorption strategies have the first priority and risky strategies have the last priority according to the prioritization. The test hypotheses that show the impact of aggressive innovative strategies, innovative strategies, pioneering innovative strategies, and risky innovative strategies on the development of the cosmetics industry were all confirmed. Managers and officials active in the cosmetics industry are suggested to help the development of the cosmetics industry by absorbing up-to-date technologies.Extended Abstract                                           IntroductionInnovation is one of the main factors in gaining the competitive advantage of companies, and in order to achieve rapid growth and success in the markets (in domestic and international arenas), companies have a great desire to use technological innovation and provide new and high-quality products (Tajadin et al., 2012). Therefore, the link between innovation and strategy is important for the effective management of innovation; and without strategy, it will not be possible for innovation to improve performance and other organizational successes (Akman & Yilmaz, 2018). Innovation helps companies to gain a competitive advantage in an uncertain environment and dominate their opponents, and this has an important effect on the company's performance in the long term; and also, it is the innovation which is the main factor that causes businesses to grow. Organizational innovation is the driver of organizational growth of the creator of future successes, and a tool that allows businesses to prove their existence in the global economy. Peter Drucker briefly states that every organization needs a core capability, and this important competency is innovation (Eidi et al, 2019). Innovation helps companies to gain a competitive advantage in an uncertain environment and dominate their opponents, and this has an important effect on the company's performance in the long term, and innovation is also the main factor that causes businesses to grow (Eyni, 2020).The industry sector is the main driver of growth, success and innovation of countries. In addition to creating added value, this sector will lead to the creation of employment more than other sectors of the economy. Adding value, creating jobs, stimulating innovation, and responding to consumer needs are key factors for long-term and sustainable economic growth. The strong flow of innovation in the field of raw materials, information technology, production and manufacturing processes, and creation of new opportunities to design and manufacture new products and services are among the issues that will lead to the country's economic growth through the industry sector (Zare, 2019). One of the main axes of entrepreneurship is innovation, and by the implementation of innovation strategies, international entrepreneurship can occur in this industry to be developed, hence the main issue in this study is: how is the presentation of effective innovative strategies on the development of the cosmetics industry with the emphasis on international entrepreneurship?Theoretical FrameworkInnovation strategyInnovation strategy in organizations is one of the central trends in recent years, and is considered very vital for organizational adaptation and restructuring and its competitive advantage. The term innovation strategy includes various components such as innovation creation, innovation adoption, and innovation diffusion. The gap that exists is that the program and components of the R&D innovation strategy process are not well structured (Parellada et al, 2021; Kim & Huarng, 2020).International entrepreneurshipInternational entrepreneurship is a creative process of discovering and exploiting opportunities outside domestic markets and in search of competitive advantage, which is a bold process of creating managerial value, through which people adopt innovative behaviors, proactively combined with calculated risk-taking, to successfully pursue foreign business opportunities arising from inefficiencies in the multinational market with the aim of achieving financial and non-financial rewards. One of the most important decisions in international entrepreneurship is choosing a strategy to enter emerging international markets. Today's emerging international entrepreneurs are more inclined towards innovation and looking for opportunities, and their participation in international activities is largely influenced by their owner or founder (Sarhadi, 2019).Saadat et al, (2023) investigated the impact of business strategies on innovative performance in order to achieve effective performance in defense industry subsidiary companies. The obtained results indicate the existence of a significant relationship between the variables of business strategy and innovative performance, and the predictive and control capabilities and flexibility of business strategies are effective in promoting innovative performance. Also, the fit indices of the model indicate that the presented model has a suitable fit.Arabshahi & Abbaszadehgaretekan (2023) investigated the effect of electronic customer relationship management on marketing performance by analyzing the mediating role of product innovation and emphasizing customer knowledge. The findings show that the electronic customer relationship management variable had a positive and significant effect on product innovation development, and the product innovation development variable also had a positive and significant effect on marketing performance. Also, customer knowledge had a positive and significant impact on marketing performance and product innovation development, and electronic customer relationship management and customer knowledge had a positive and significant impact on marketing performance through product innovation development.Research methodologyThe research method is applicable in terms of its purpose, and qualitative in terms of its implementation. The statistical population of the research includes 7 managers and officials of Sehat Industrial and Trading Company and 3 academic experts. The data collection tool is interview.Research findingsTo analyze the research data, theme analysis; which is a method to determine, analyze, and express of the patterns (themes) in the data, as well as MAXQDA software was used. According to the obtained results, the innovation strategies are: aggressive innovative strategies, innovative technology absorption strategies, pioneering innovative strategies, risky innovative strategies, among which the innovative technology absorption strategies have the first priority and risky strategies have the last priority according to the prioritization. The test hypotheses that show the impact of aggressive innovative strategies, innovative strategies, pioneering innovative strategies, and risky innovative strategies on the development of the cosmetics industry were all confirmed. Managers and officials active in the cosmetics industry are suggested to help the development of the cosmetics industry by absorbing up-to-date technologies.ConclusionThe current research was conducted with the aim of providing effective innovative strategies in the development of the cosmetics industry with an emphasis on international entrepreneurship. The results of this research are in agreement with the results of Saadat et al, (2023), Arabshahi & Abbaszadehgaretekan (2023), Bauj Khushmian & sadoughi (2022), Zahra et al, (2022), Eshkor Vakili & nojabaei (2022), Kral & Janoskova (2021), Eyni (2020), and Beyene et al, (2016). Zahra et al, (2022) presented the definitions of corporate innovation strategy and diverse opinions of authors around the world about the realization and analysis of strategy in economic enterprises. Regarding the most important results obtained from issues, needs, and opportunities; this study highlights the insufficient knowledge about formulation and implementation of innovation strategies. Moreover, it emphasizes the lack of information about the importance of innovative activity as a capability that can be systematically developed within the framework of an innovation strategy, regarding input, transformation process, and production.According to the results of the research, the following suggestions are presented:1- The managers of the company should make the necessary investments to import new technologies using expert staff to provide more qualitative products and services in global markets.2- Importance should be given to knowledge management because this will lead to better and more correct decisions by managers.